Kualitas Spermatozoa Ayam Bangkok dalam Pengencer Ringer Laktat dan Air Kelapa yang Disuplementasi Kuning Telur dan Glukosa: Quality of Bangkok Chicken Spermatozoa in Lactate Ringer and Coconut Water Extender Supplemented with Egg Yolk and Glucose - Saefudding Saefudding; Khaeruddin Khaeruddin; Bahri Syamsuryadi (Anoa: Journal of Animal Husbandry, 2023)
Semen preservation can be done by freezing or cold storage (chilling). The purpose of this study was to determine the effect of the type of semen extender on the quality of Bangkok chicken spermatozoa, and to determine the best type of extender used for Bangkok chicken spermatozoa. This study used a completely randomized design (CRD) with six treatment levels (P1, P2, P3, P4, P5, P6) with four replications. The treatment level used was: P1 = Coconut Water, P2 = Coconut water + Egg Yolk, P3 = Coconut Water + Egg Yolk + Glucose, P4 = Ringer Lactate, P5 = Ringer Lactate + Egg Yolk, P6 = Ringer Lactate + Egg Yolk + Glucose. Parameters observed were motility, viability, and abnormality. The results showed that the type of extender treatment had a very significant effect (P<0.01) on spermatozoa motility, spermatozoa viability, and spermatozoa abnormalities. The conclusion of this study is that the effect of the type of semen extender on the quality of spermatozoa in Bangkok chickens is very significant, especially with the addition of egg yolk components. The best type of extender to use is coconut water extender with the addition of egg yolk.